(untitled) (Semiárida, 2020)
lnformation about Tetrachne dregei Nees as a cultivated pasture is not available. The main purpose of this work was to determine the germination percentage (G.P.) of Tetracne disseminules under different treatments - Le. Physicals (pre- chilling and pre-washíng), hormonals (plant hormones: AG 3, CCC, ANA) and not-treated controls. Germination tests were performed on petri dishes in growth chamber with controlled photo and thermoperiod. Tukey test was used for mean significance differences. Higher G.P. was obtained from heavier caryopsis. Germination at 48 hours of caryopsis Oight and heavy) excessed that of the anthecium. Treatments didn’t enhance G.P. of anthecium and caryopsis. Leaves and root development of seedlings were affected by growing regulators.